2008
DOI: 10.1158/1055-9965.epi-07-0536
|View full text |Cite
|
Sign up to set email alerts
|

Cord Serum Estrogens, Androgens, Insulin-Like Growth Factor-I, and Insulin-Like Growth Factor Binding Protein-3 in Chinese and U.S. Caucasian Neonates

Abstract: Markedly lower breast cancer incidence rates in Asians than Caucasians are not explained by established adult risk factors. Migration studies suggest the importance of early-life exposures, including perhaps the in utero period. Concentrations of steroid hormones and insulin-like growth factors (IGF) were measured in umbilical cord sera from pregnancies in Shanghai, China (n = 121) and Boston, MA (n = 111). Pregnancy characteristics were ascertained by interview and medical records. Means and percent differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
5
9
2
Order By: Relevance
“…Our finding of higher cord blood levels of IGF-1 among Caucasian compared with Asian newborns is of particular importance because, in the same dataset, maternal pregnancy estradiol and estriol (Lipworth et al, 1999), as well as cord blood estriol, androstenedione, and testosterone (Troisi et al, 2008) have been reported to be significantly higher among Chinese than among Caucasian women. In a small subsample of 52 US and 22 Chinese newborns from the same dataset, in which IGF-2 was not measured, there was no significant difference between the two groups with respect to cord blood IGF-1 and, possibly by chance owing to the small subsample size, levels of IGF-1 appeared to be somewhat higher among Chinese newborns (Troisi et al, 2008). Our results indicating that IGF-1 dominates foetal growth among Caucasians, whereas IGF-2 plays a similar role among Asians and that associations are evident among taller mothers are not directly comparable with previous studies, because mutual adjustment of IGF-1 and IGF-2 and stratification by maternal height were not generally undertaken.…”
Section: Discussionsupporting
confidence: 50%
“…Our finding of higher cord blood levels of IGF-1 among Caucasian compared with Asian newborns is of particular importance because, in the same dataset, maternal pregnancy estradiol and estriol (Lipworth et al, 1999), as well as cord blood estriol, androstenedione, and testosterone (Troisi et al, 2008) have been reported to be significantly higher among Chinese than among Caucasian women. In a small subsample of 52 US and 22 Chinese newborns from the same dataset, in which IGF-2 was not measured, there was no significant difference between the two groups with respect to cord blood IGF-1 and, possibly by chance owing to the small subsample size, levels of IGF-1 appeared to be somewhat higher among Chinese newborns (Troisi et al, 2008). Our results indicating that IGF-1 dominates foetal growth among Caucasians, whereas IGF-2 plays a similar role among Asians and that associations are evident among taller mothers are not directly comparable with previous studies, because mutual adjustment of IGF-1 and IGF-2 and stratification by maternal height were not generally undertaken.…”
Section: Discussionsupporting
confidence: 50%
“…Serum was aliquoted in 2 mL vials and immediately frozen at -70° C. Quantification of 25(OH)D, IGF-1, and IGFBP-3 was performed at the Reproductive Endocrine Research Laboratory at the University of Southern California, using previously described techniques [19, 20]. 25(OH)D was measured using a commercial 125 I-based radioimmunoassay (RIA) kit (DiaSorin, Stillwater, MN), with a preliminary organic solvent extraction step.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, estradiol levels are overall not dramatically different between RIA and mass spectrometry-based studies [with the exception of the study by Lagiou et al (46)]. Closer inspection of the immunoassay studies, which reported the lowest testosterone values reveals that these assays employed column purification to help remove interfering cross-reacting steroids (24, 25, 53). Nevertheless, these studies still reported values about 40% higher than those reported by the largest study to date which employed an extensively validated and internally controlled LC–MS/MS assay (22), suggesting that chromatographic treatment was not completely effective in removing all cross-reacting compounds prior to RIA analysis.…”
Section: Issues Related To the Determination Of Steroid Concentrationmentioning
confidence: 98%
“…Organic solvent extraction has been employed in most studies to remove interfering factors in order to improve specificity, accuracy, and sensitivity. A few studies have used additional column purification techniques (24, 25, 53) to address concerns regarding the accuracy of RIAs for the measurement of low concentrations of steroids, in particular, testosterone (56, 57). However, while the assays are sometimes tested and validated for use in female or pediatric samples, their suitability for umbilical cord blood analysis is usually assumed and invariably not adequately tested.…”
Section: Issues Related To the Determination Of Steroid Concentrationmentioning
confidence: 99%